THE ROLE OF LATIN TERMS IN MEDICINE - Normurodova Sohiba; Aitmuratova Perkhan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The main purpose of this article is to determine the direct role and place of the Latin language in modern society, to identify social spheres in which the Latin language is the most important part, to determine the level of understanding in society of the role of the Latin language in the modern world.